2022
DOI: 10.3390/clinpract12050080
|View full text |Cite
|
Sign up to set email alerts
|

Approach to Thromboprophylaxis for Prevention of Venous Thromboembolism in COVID-19: Global Updates and Clinical Insights from India

Abstract: Venous thromboembolism (VTE) frequently occurs in patients with coronavirus disease-19 (COVID-19) and is associated with increased mortality. Several global guidelines recommended prophylactic-intensity anticoagulation rather than intermediate-intensity or therapeutic-intensity anticoagulation for patients with COVID-19-related acute or critical illness without suspected or confirmed VTE. Even though standard doses of thromboprophylaxis are received, many cases of thrombotic complications are reported; hence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…An outline was framed and concluded (Parakh, Kakkar & Kakkar, 2007). Ramakrishnan et al, (2022) had also suggested adherence to ACCP guidelines in VTE prevention. Shirol et al (2017) conducted a survey, where the majority of plastic surgeons admitted the usage of low molecular heparin after considering the patient's age, comorbidities, degree and percentage of burn and lower limb involvement.…”
Section: Discussionmentioning
confidence: 99%
“…An outline was framed and concluded (Parakh, Kakkar & Kakkar, 2007). Ramakrishnan et al, (2022) had also suggested adherence to ACCP guidelines in VTE prevention. Shirol et al (2017) conducted a survey, where the majority of plastic surgeons admitted the usage of low molecular heparin after considering the patient's age, comorbidities, degree and percentage of burn and lower limb involvement.…”
Section: Discussionmentioning
confidence: 99%
“…COVID‐19 infection is associated with a hypercoagulable state and risk of thromboembolism 1 . Variability exists in the prevention of venous thromboembolism among hospitalised patients with COVID‐19 2,3 . While several guidance documents have been published, 4–6 a formal clinical practice guideline using evidence from randomised clinical trials and well‐designed observational studies was recently issued by the International Society of Thrombosis and Haemostasis 7 …”
Section: Introductionmentioning
confidence: 99%
“…Hence, appropriate and adequate thromboprophylaxis is critical for VTE prevention in COVID-19. In this journal, Ramakrishnan et al [ 4 ] reviewed the available global literature, providing clinical insights into our approach towards managing VTE in patients with COVID-19. Furthermore, they summarized the incidence and risk factors for VTE with an emphasis on the thromboprophylaxis approach in hospitalized patients and special populations with COVID-19, assessing clinical implications in their Indian context.…”
mentioning
confidence: 99%